Counseling Services for Women in Marriage Age - Frischa Meivilona Yendi; Zadrian Ardi; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
Marriage is a bond between the outer and inner man as a husband who has not aged 25 years and women 21 years old wife is not with the purpose of achieving happiness. Marriage and family counseling is a profession that will be developed in Indonesia. Counseling emphasizes on changes contained in the family system. Stages counseling, theory and dynamics as well as the use of counseling skills in marriage and family counseling has similarities with individual counseling and group counseling.